Fine capsule variation affects bacteriophage susceptibility in Klebsiella pneumoniae ST258. Issue 8 (29th June 2020) - Venturini, Carola; Ben Zakour, Nouri L.; Bowring, Bethany; Morales, Sandra; Cole, Robert; Kovach, Zsuzsanna; Branston, Steven; Kettle, Emma; Thomson, Nicholas; Iredell, Jonathan R.
Abstract: Multidrug resistant (MDR) carbapenemase‐producing (CP) Klebsiella pneumoniae, belonging to clonal group CG258, is capable of causing severe disease in humans and is classified as an urgent threat by health agencies worldwide. Bacteriophages are being actively explored as therapeutic alternatives to antibiotics. In an effort to define a robust experimental approach for effective selection of lytic viruses for therapy, we have fully characterized the genomes of 18  Kumoniae target strains and tested them against novel lytic bacteriophages (n = 65). The genomes of K pneumoniae carrying bla NDM and bla KPC were sequenced and CG258 isolates selected for bacteriophage susceptibility testing. The local K pneumoniae CG258 population was dominated by sequence type ST258 clade 1 (86%) with variations in capsular locus ( cps ) and prophage content. CG258‐specific bacteriophages primarily targeted the capsule, but successful infection is also likely blocked in some by immunity conferred by existing prophages. Five tailed bacteriophages against K pneumoniae ST258 clade 1 were selected for further characterization. Our findings show that effective control of K pneumoniae CG258 with bacteriophage will require mixes of diverse lytic viruses targeting relevant cps variants and allowing for variable prophage content. These insights will facilitate identification and selection of therapeutic bacteriophage candidates against this serious pathogen.